Synthesis and Antifungal Activity of Some 3-[5´ -Aryl-3´ -Mercapto-1´ , 2´ , 4´ -Triazol-4´ -yl]-2-Aryl-4-Thiazolidinones - Giri, S.; Khan, M.H. (Asian Journal of Chemistry, 2010)
A number of [3-5´-aryl-3´-mercapto-1´, 2´, 4´-triazol-4´-yl]-2-aryl-4-thiazolidinones have been synthesised by the cyclocondensation of mercapto acetic acid and anlls. Their antifungal activities have been screened against A. niger and H. oryzae.